A escrita de si em Boyhood, de J. M. Coetzee - Amaral, João Pedro Wizniewsky (2016)
Boyhood (1997) is the first volume of Scenes from Provincial Life trilogy, written by the South-African J. M. Coetzee. Boyhood’s narrative has peculiar characteristics for an autobiographical novel, as the third person narrator and the use of Present Simple. This research’s hypothesis is that the protagonist, the boy John Coetzee, discovers himself and discovers himself within the apartheid regime; and this self-discovery is not done through the form of teaching or reporting from a conscious and rational narrative. The process of discovering himself within this regime occurs through its infantile conscience, puerile observations and the construction of the general protagonist’s perception. From this hypothesis, we discuss in this dissertation selfwritting narratives and traditional confessional narratives in literature, based on Coetzee’s theoretical studies, to later analyze some of the main features of the narrative in this novel to verify how non-religious confession techniques are present in Boyhood. Coetzee manipulates these confessional techniques avoiding the typical confessional narrative, present in authors like Augustine, J. J. Rousseau and Dostoevsky. In this study, we also observe that the narrative episodes are based on confession, a self-investigating method that highlights painful contents to be confessed. Among these contents, we noticed the feelings of guilt and shame are recurrent in most the protagonist’s experiences. Confessional narrative is a method that Coetzee uses to debug knowledge and to select themes presented in Boyhood, differently from traditional confessional narratives.